Cinema Africa 2019 - Interview A. Forjaz: "Racism in Mozambique today" (short clip 5) (Cinema Africa 2019, 2020)
The film festival of the Africa Multiple Cluster of Excellence "Cinema Africa" took place in November 2019. During the course of 4 days it showed four extraordinary films with African context. In this interview the producer and cinematographer Antonio Forjaz talked with Dr. Gilbert Ndi Shang about this year's contribution "Resgate - Redemption" from Maputo, Mozambique. Cinema Africa 2019 was the 11th edition of the renowned Bayreuth African Film Festival. It has been founded and is curated by Prof. Dr. Ute Fendler. Find out more: https://www.africamultiple.uni-bayreuth.de/en/news/2019/Cinema_Africa_recap/index.html